A Universal Error Correction Method for Memristive Stateful Logic Devices for Practical Near‐Memory Computing. (24th June 2020) - In, Jae Hyun; Kim, Young Seok; Song, Hanchan; Kim, Gwang Min; An, Jangho; Jeon, Jae Bum; Kim, Kyung Min
Abstract : Memristive stateful logic allows complete in‐memory computing and is considered to be a next‐generation computing technology for low power edge applications. Since the first stateful IMP gate was proposed in 2010, few studies have yet addressed the operating reliability issues that should be resolved before the technology is practically realized. Herein, a feasible near‐memory error correction method for a typical bipolar‐type memristor stateful logic system is proposed. An error correction principles using a HfO2 ‐based crossbar array device is explained, and two types of error correction methods checking if the number of FALSE data is zero and if the number of TRUE data is odd are proposed. Although the error correction modules require additional circuits and processing time, the resulting computing efficiency is comparable with conventional stateful logic techniques. Its application with a one‐bit full adder is demonstrated and its feasibility for practical stateful logic devices is validated. Abstract : A universal error correction method for a memristive stateful logic device is proposed. With the method, the inevitable errors can be completely corrected with the help of a near‐memory error correction circuit. A successful demonstration of a one‐bit full adder confirmed that the method is feasible for the practical stateful logic device.